Does energy-environmental Kuznets curve hold for Ethiopia? The relationship between energy intensity and economic growth - Shemelis Kebede Hundie; Megersa Debela Daksa (Journal of Economic Structures, 2019)
Reducing energy intensity is an important element for Ethiopia to achieve its ambitious climate-resilient growth goals. Understanding the factors that determine energy intensity plays a crucial role for academics and policymakers to formulate sound energy conservation and energy efficiency policies. This article investigates drivers of energy intensity in Ethiopia over the period of 1974-2014. The ARDL bounds test approach to cointegration and FMOLS-based Hansen parameter instability test methods were applied to examine the long-run relationship among the variables. The result reveals that there is an inverted U-shape or Environmental Kuznets curve-type relationship between economic growth and energy intensity, implying that economic growth at early (industrialization) stage of development spurs energy intensity while delinking occurs at the later stages of development. Urbanization increases energy intensity, while impact of import is negative. The Toda-Yamamoto Granger causality test result shows a bidirectional causal relationship between import and energy intensity. Moreover, energy intensity Granger causes aid and industrialization.
Keywords: 330; Energy intensity; Economic growth; FMOLS; ARDL; Ethiopia